Phosphorus sorption in some soils of the semi-arid region of the Brazilian Northeast - Pereira, José Ribamar; Faria, Clementino Marcos Batista de (Pesquisa Agropecuaria Brasileira, 1998)
This work was carried out in fifteen soil samples of the semi-arid region of the Brazilian Northeast. The soils were the following: five Vertisols (V), three Red Yellow Latosols (LVa), two Red Yellow Podzolic (PVa), one Carbonatic Cambisol (CbCarb.), one eutrophic Red Dark Latosol (LVEe), one Vertic Cambisol (CbV), one Latossolic Cambisol (CbL), and one non Calcic Brown (BnCa). The objective was to evaluate, through the Langmuir isotherm, the capacity of phosphorus sorption by these soils. The results obtained showed that the phosphorus sorption by the soils varied from 0.124 to 0.805 mg P/g. It was higher in the alkaline soils (V, CbCarb, CbV, and CbL) and lower in the acid soils (LVa and PVa). The maximum phosphorus sorption correlated positively with pH, water content at 0.3 bar, CTC, organic matter, clay content and exchangeable calcium and magnesium.